Deletion of IL-6 Exacerbates Colitis and Induces Systemic Inflammation in IL-10-Deficient Mice. (3rd November 2019) - Ye, Mei; Joosse, Maria E; Liu, Ling; Sun, Yu; Dong, Ying; Cai, Changchun; Song, Zhenmei; Zhang, Jennifer; Brant, Steven R; Lazarev, Mark; Li, Xuhang
Abstract: Background and Aims: Interleukin 6 [IL-6] or its receptor is currently a candidate for targeted biological therapy of inflammatory bowel disease [IBD]. Thus, a comprehensive understanding of the consequences of blocking IL-6 is imperative. We investigated this by evaluating the effects of IL-6 deletion on the spontaneous colitis of IL-10-deficient mice [IL-10 −/− ]. Methods: IL-6/IL-10 double-deficient mice [IL-6 −/− /IL-10 −/− ] were generated and analysed for intestinal inflammation, general phenotypes and molecular/biochemical changes in the colonic mucosa compared with wild-type and IL-10 −/− mice. Results: Unexpectedly, the IL-6 −/− /IL-10 −/− mice showed more pronounced gut inflammation and earlier disease onset than IL-10 −/− mice, both locally [colon and small bowel] and systemically [splenomegaly, ulcerative dermatitis, leukocytosis, neutrophilia and monocytosis]. IL-6 −/− /IL-10 −/− mice exhibited elevations of multiple cytokines [IL-1β, IL-4, IL-12, TNFα] and chemokines [MCP-1 and MIG], but not IFN-γ [Th1], IL-17A and IL-17G [Th17], or IL-22 [Th22]. FOXP3 and TGF-β, two key factors for regulatory T [Treg] cell differentiation, were significantly down-regulated in the colonic mucosa, but not in the thymus or mesenteric lymph nodes, of IL-6 −/− /IL-10 −/− mice. CTLA-4 was diminished while iNOS was up-regulated in the colonic mucosa of IL-6 −/− /IL-10 −/− mice. Conclusion: In IL-10 −/− mice, complete IL-6 blockade significantly aggravates gut inflammation, at least in part by suppressing Treg/CTLA-4 and promoting the IL-1β/Th2 pathway. In addition, the double mutant exhibits signs of severe systemic inflammation. Our data define a new function of IL-6 and suggest that caution should be exercised when targeting IL-6 in IBD patients, particularly those with defects in IL-10 signalling.